Identification of a Novel RING Finger Protein as a Coregulator in Steroid Receptor-Mediated Gene Transcription - Moilanen, Anu-Maarit (American Society for Microbiology, 1998)
Using the DNA-binding domain of androgen receptor (AR) as a bait in a yeast two-hybrid screening, we have identified a small nuclear RING finger protein, termed SNURF, that interacts with AR in a hormone-dependent fashion in both yeast and mammalian cells. Physical interaction between AR and SNURF was demonstrated by coimmunoprecipitation from cell extracts and by protein-protein affinity chromatography. Rat SNURF is a highly hydrophilic protein consisting of 194 amino acid residues and comprising a consensus C(3)HC(4) zinc finger (RING) structure in the C-terminal region and a bipartite nuclear localization signal near the N terminus. Immunohistochemical experiments indicated that SNURF is a nuclear protein. SNURF mRNA is expressed in a variety of human and rat tissues. Overexpression of SNURF in cultured mammalian cells enhanced not only androgen, glucocorticoid, and progesterone receptor-dependent transactivation but also basal transcription from steroid-regulated promoters. Mutation of two of the potential Zn(2+) coordinating cysteines to serines in the RING finger completely abolished the ability of SNURF to enhance basal transcription, whereas its ability to activate steroid receptor-dependent transcription was maintained, suggesting that there are separate domains in SNURF that mediate interactions with different regulatory factors. SNURF is capable of interacting in vitro with the TATA-binding protein, and the RING finger domain is needed for this interaction. Collectively, we have identified and characterized a ubiquitously expressed RING finger protein, SNURF, that may function as a bridging factor and regulate steroid receptor-dependent transcription by a mechanism different from those of previously identified coactivator or integrator proteins.